Ship Dynamics and Hydrodynamics - Guedes Soares, Carlos; Sutulo, Serge (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The reprint presents a collection of contributions to various aspects of ship hydrodynamics and dynamics, a part of which was presented at the MARTECH2020 Conference, and all of which were published in a Special Issue of the journal, Marine Science and Engineering. The scope of the collection covers nearly all branches of ship hydrodynamics and dynamics, and so it may be of interest to all specialists in the field as well as for naval architects and applied mechanicians of various levels. The authors are recognized specialists from a number of countries, and to all of whom the Editors express their acknowledgement.